Iowa RBA, October 20, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for October 20, 1997. Highlights of the update include the continued presence of Eurasian Collared Doves and sightings of a Sabine's Gull and a Lesser Black-backed Gull. Also of note was the observation of ten species of Sparrows at the Hawkeye Wildlife Management Area, including Nelson's Sharp-tailed and Harris'. Also included are handwritten notes for the next week's update with sightings of Pine Siskins, Purple Finches, and a Red Crossbill. Epson - sheet feed/flatbed